ANALISIS KEPUTUSAN PEMBELIAN PADA CONVENIENCE STORE - Kasmad, Mr (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the Effect of Store Atmosphere and Prices on Consumer Purchasing Decisions at 7-Eleven Store Convenience. To test the effect of  independent variables on dependent, quantitative approaches and associative methods are used. The analytical method used is multiple linear regression analysis with a sample of 98 and the sampling technique used is the Accidental Sampling. Hypothesis test results indicate that Store Atmosphere has a positive and significant effect on purchasing decisions with a regression coefficient of 0.277. Price has a positive and significant effect on purchasing decisions with a regression coefficient of 0.787. Simultaneously Store Atmosphere and price has positive and significant effect on purchasing decisions with coefficient of determination of 87.3%, while the remaining 12.7% is explained by other variables outside this study, for example location, service quality, promotion, and consumer trust